Posttranslational modification and plasma membrane localization of the Drosophila melanogaster presenilin. - Nowotny, P.; Gorski, S.M.; Han, S.W.; Philips, K.; Ray, W.J.; Nowotny, V.; Jones, C.J.; Clark, R.F.; Cagan, R.L.; Goate, A.M. (Molecular and Cellular Neurosciences, 2000)
Mutations in two genes, presenilin 1 (PS1) and presenilin 2, are linked to early onset cases of familial Alzheimer's disease. The presenilins are thought to contribute to the pathogenesis of Alzheimer's disease by directly or indirectly affecting the proteolytic processing of the amyloid precursor protein. They have also been implicated in the proteolytic processing of Notch. In PS1-deficient mammalian cells, the proteolytic release of the Notch intracellular domain is reduced. Likewise, loss-of-function mutations in Drosophila presenilin (Psn) prevent the production of the intracellular Notch signaling fragment and lead to phenotypes resembling Notch mutants. Here we characterize the Drosophila Psn protein and demonstrate that it undergoes a proteolytic cleavage. We describe Psn expression at different developmental stages of the fly and show Psn localization near both apical and basal plasma membranes. Furthermore, we demonstrate that portions of the Psn protein span the plasma membrane in S2 cells.